Ultra maniac - Yoshizumi, Wataru (San Francisco, CA : Viz Media, 2005)
When Nina Sakura, a transfer student from a witch school in another dimension, enrolls at a middle school in Japan, she strives to improve her grades, make friends, and practice love spells on her unsuspecting classmates.
Chiefly illustrations.
"Second printing, November 2005"--Colophon, v. 1.
"Rated: A for all ages"--Back cover, v. 1.
Translated from the Japanese.
Keywords: Junior high school students -- Comic books, strips, etc; Witches -- Comic books, strips, etc; Junior high school students; Witches; Manga comics; Comic books, strips, etc; Graphic novels; Children's stories -- Comic books, strips, etc; Graphic novels